CLUSTER ANALYSIS OF SOUTHERN PERU TOURIST WITH TOOLS GEOMARKETING - Navarrete, Mónica (2015)
Began using several years the cluster concept to describe the competitive advantage of interconnected companies in a particular sector, it is evident that behind the cluster are tourist destinations. Think of tourism as a cluster involves moving from a segmentation by product and territory, a segmentation of a circuit in which several companies with the local population , are coordinated to cater to a tourist who visit attractions that are way to your destination finally, in order to maximize your time and money. In this paper, we analyze the South Peruvian tourism circuit by applying tools of spatial analysis Geomarketing places that make up the circuit to take advantage of the attractions of the area in an integrated manner.